1985
DOI: 10.1111/j.1365-2605.1985.tb00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of semen parameters in a large group of normal Chinese men

Abstract: Testicular size, semen characteristics and serum reproductive hormone levels were studied in 1239 normal Chinese men. The mean testicular size of 17 ml in this group of subjects was similar to other reports in Orientals but was smaller than that reported in Caucasians. Semen volume, and the sperm count, motility and morphology were comparable to those described for Caucasian subjects. The cervical mucus penetration test (Kremer's test) and the zona-free hamster egg penetration test were also studied in some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 29 publications
(19 reference statements)
3
27
3
3
Order By: Relevance
“…Several other studies did not find any differences among men of different ages in their semen volume, 18,19 while one reported an increase in volume with age. 20 As such, while the majority of studies suggest that a decrease in semen volume with paternal age occurs, the exact relationship is unclear.…”
Section: Effect Of Paternal Age On Semen Qualitymentioning
confidence: 81%
See 1 more Smart Citation
“…Several other studies did not find any differences among men of different ages in their semen volume, 18,19 while one reported an increase in volume with age. 20 As such, while the majority of studies suggest that a decrease in semen volume with paternal age occurs, the exact relationship is unclear.…”
Section: Effect Of Paternal Age On Semen Qualitymentioning
confidence: 81%
“…To add to the controversy, two studies found an increase in sperm motility in relation to increasing age, with a 0.06% increase for each year of age. 19,20 On the whole, however, there appears to be a preponderance of evidence to suggest that APA is associated with decreased sperm motility.…”
Section: Effect Of Paternal Age On Semen Qualitymentioning
confidence: 99%
“…A diminuição do percentual de espermatozóides móveis, observada em 12 das 20 publicações 7,12,13,[15][16][17][18][19][20][21][22][23] , foi mais freqüente, sendo mais evidente quando houve controle no período de abstinência. A média de redução da motilidade anual variou de 0,3 13 a 0,7% 7 .…”
Section: Discussionunclassified
“…Many studies in the literature have suggested a decline in semen quality and quantity over time (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). …”
Section: Discussionmentioning
confidence: 99%
“…In 1951, MacLeod and Gold's study had set the minimal sperm count of 20 X 106 as a statistically significant important parameter for male fertility; the mean density for fertile man in their study was 107 X 106 (2). Since then, a number of studies have suggested an international decline in semen quality over the last several decades (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Recently, in a metaanalysis of 61 studies worldwide, Carlesen et aL reported a trend toward decreasing sperm densities and volume of seminal fluid over the past 50 years (8)° On the other hand, other studies (13)(14)(15)(16) have shown no decrease in semen quality over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%